2008
DOI: 10.1007/s00436-008-1071-8
|View full text |Cite
|
Sign up to set email alerts
|

Climate or host availability: what determines the seasonal abundance of ticks?

Abstract: Ticks can significantly affect the health and fitness of the host. Seasonal population dynamics of ticks play a vital role in disease transmission and the shaping of life-history traits of both tick and host. In this study, we examine the seasonal population dynamics of Ixodes hirsti in South Australia. For 2 years, we measured the prevalence and intensity of I. hirsti on passerines on Kangaroo Island. Ticks were present on birds from April to November and absent from December to March, with a peak in tick pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 43 publications
(38 reference statements)
0
33
0
Order By: Relevance
“…Therefore, given that we observed more aerial insect feeding in island than mainland birds, lower mass in island birds may be selected for given their differences in feeding ecology. Although body mass is prone to diurnal and seasonal variation linked to fluctuations in food availability, parasite prevalence, and other ecological factors that can act at a regional scale (Creswell 1998;Oorebeek and Kleindorfer 2008), even when controlling for season, island birds had significantly lower body mass. Bill length is a highly heritable quantitative trait (Keller et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, given that we observed more aerial insect feeding in island than mainland birds, lower mass in island birds may be selected for given their differences in feeding ecology. Although body mass is prone to diurnal and seasonal variation linked to fluctuations in food availability, parasite prevalence, and other ecological factors that can act at a regional scale (Creswell 1998;Oorebeek and Kleindorfer 2008), even when controlling for season, island birds had significantly lower body mass. Bill length is a highly heritable quantitative trait (Keller et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Ambush ticks are expected to be more sensitive to short distance cues, like body heat and light intensity, which alert a tick to the presence of a possible host (Howell 1975). Birds that descend to ground level for foraging or drinking are presumed to be the common host for larval I. hirsti (Oorebeek and Kleindorfer 2008a). Because birds do not remain stationary for long periods of time while at ground level, larvae will have insufficient time to 'hunt' for their host.…”
Section: Discussionmentioning
confidence: 99%
“…Larval I. hirsti have only been recorded on passerines in South Australia (Kleindorfer et al 2006;Oorebeek and Kleindorfer 2008a). Field studies have shown that many tick species are attracted to a CO 2 source at a distance of 4 m (Wilson et al 1972;Koch 1987;Adeyeye and Butler 1991;Solberg et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to host factors, because ectoparasites tend to be more exposed to the environment than most other parasites, environmental factors may be particularly critical in determining prevalence, intensity, and richness of ectoparasitism (Cumming and Van Vuuren, 2006;Oorebeek and Kleindorfer, 2008;Merino and Møller, 2010;Malenke et al, 2011). Such factors influence fleas both indirectly, via their effects on many host characteristics, and directly, as many fleas spend much of their lives detached from the host and, even when attached to the host, generally remain in direct contact with the external environment (Krasnov et al, 2002b).…”
mentioning
confidence: 99%